Analysis of Mathematics Problem Solving Ability Based on Polya Problem Solving Steps - Sapri, Hasri Amaliah (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This research is a descriptive study with a qualitative approach that aims to describe the ability of students' mathematical problem-solving classes. The instruments in this study were a logical-mathematical intelligence test, a problem-solving ability test, and an interview guide. Data collection in this study was carried out using test, interview, and observation techniques. Checking the validity of the data carried out in this study was a technical triangulation. The results of this study indicate students' ability to solve mathematical problems based on Polya's problem-solving steps: (1) Understanding the problem, subjects who are able to correctly determine what is known and asked about the problem are subjects with high and moderate logical-mathematical intelligence, whereas subjects with low logical-mathematical intelligence are only able to determine things that are known in the problem and have not been able to determine what is being asked in the problem; (2) Develop a problem-solving plan, subjects who are able to develop relevant problem-solving plans to solve problems appropriately and find relationships between things that are known to find things needed in solving problems are subjects with high logical-mathematical intelligence, then for subjects with moderate logical-mathematical intelligence are only able to find connections between things that are known, whereas subjects with low logical-mathematical intelligence are not yet able to devise relevant problem-solving plans and find relationships between things that are known; (3) Carry out the plan, subjects who are able to carry out the steps of the problem solving plan correctly, are skilled in performing arithmetic operations, and find the right solution to the problem are subjects with high logical-mathematical intelligence, while subjects with moderate logical-mathematical intelligence and low ability to carry out a solution plan that is made even though it is not relevant to solving problems and less skilled in performing arithmetic operations, so that the right solution to the problem cannot be found; and (4) Re-checking, subjects who are able to interpret the solutions to the problems that have been obtained and re-examine the steps and calculation results are subjects with high, medium, and low logical-mathematical intelligence.